Magnetic Properties of Carbon-Encapsulated Ni Core-Shell Structure Nanoparticles by DC Arc Plasma - Wu, X.J.; Wei, Z.Q.; Chen, X.J.; Wang, X.; Feng, W.J.; Yang, H.; Jiang, J.L. (Asian Journal of Chemistry, 2014)
Carbon encapsulated nickel nanoparticles were prepared via DC arc plasma process. The composition, morphologies, microstructure, particle size and magnetic properties of the particles were characterized via X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), X-ray energy dispersive spectrometry (XEDS) and vibrating sample magnetometer (VSM). The experiment results show that the carbon encapsulated nickel nanoparticles possesses clear core-shell structure. The core of the particles is face centered cubic structure Ni and the shell is carbon. The particles are scattered homogeneously in spherical or ellipsoidal shapes. The particle size of the nanocapsules ranges from 15-40 nm with the average value about 30 nm. The particle diameter of the core is about 18 nm and the thickness of the shells is about 6-8 nm and the magnetic properties of the products are paramagnetic at room temperature.